Food insecurity and depression among low-income adults in the USA: does diet diversity play a role? Findings from the 2013–2014 National Health and Nutrition Examination Survey. Issue 7 (16th May 2021) - Narcisse, Marie-Rachelle; Felix, Holly C; Long, Christopher R; English, Emily S; Bailey, Mary M; McElfish, Pearl A
Abstract: Objective: Food insecurity is associated with a greater risk of depression among low-income adults in the USA. Members of food-insecure households have lower diet diversity than their food-secure counterparts. This study examined whether diet diversity moderates the association between food insecurity and depression. Design: Multiple logistic regression was conducted to examine independent associations between food insecurity and depression, between diet diversity and depression, and the moderating effect of diet diversity in the food insecurity–depression link. Setting: Cross-sectional data from the National Health and Nutrition Examination Survey (2013–2014). Participants: 2636 low-income adults aged 18 years and older. Results: There was a positive association between food insecurity and depression among low-income adults. Diet diversity was not associated with depression. Diet diversity had a moderating effect on the association between food insecurity and depression among low-income adults. Conclusions: Food insecurity is independently associated with depression among low-income adults in the USA. However, this association differs across levels of diet diversity. Longitudinal studies are needed to confirm the role diet diversity may play in the pathway between food insecurity and depression.